Barnamaj Taelim Maharat Alkalam Walkitabat Allughat Alearabiat Fii Almadrasat Almutawasitat Al'iislamiat Almutakamilat Al'iimam Alnawawii Pekanbaru - Siregar, Hajarol; Ibrahim, Rusdi; Hidayat, Nandang Sarip (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2024)
هدفت هذه الدراسة إلى التعرف على برنامج تخطيط تعلم مهارة التحدث والتعرف على برنامج تنفيذ تعلم مهارة التحدث. 3. التعرف على برنامج تخطيط تعلم مهارة الكتابة والتعرف على برنامج تنفيذ مهارة الكتابة. هذه الدراسة وصفية نوعية. وتم جمع البيانات من خلال: الملاحظة والمقابلات والتوثيق. وكانت نتائج هذه الدراسة: 1. التخطيط لبرنامج تعلم مهارة التحدث باللغة العربية بدءًا من: صياغة الأهداف، جدولة مواد اللغة العربية، إعداد المعلمين الأكفاء، وضع البرامج، تحديد الوسائل المناسبة، تحديد الطريقة المناسبة. 2. تنفيذ برنامج تعلم مهارة التحدث باللغة العربية: حفظ 5 كلمات من المفردات العربية كل صباح، كتابة الطلاب للمفردات الشفهية في دفاتر، تعيين المعلمين والطلاب للإشراف على اللغة، معاقبة الطلاب الذين لا يتكلمون العربية، تكرار النطق وحفظ المفردات قبل صلاة العصر كل يوم. 3. التخطيط لبرنامج تعلم مهارة الكتابة باللغة العربية: تحليل القدرات الأولية للطلاب، تحديد الأهداف، تحديد الطريقة المناسبة، تحديد أداة القياس أو التقييم المناسبة. 4. تنفيذ برنامج تعليم مهارة الكتابة باللغة العربية: يكتب الطلبة كل صباح 5 كلمات من المفردات، ويشرح المعلم قبل صلاة العصر يومياً قواعد كتابة المفردات الصحيحة، ويقيم مسابقات في كتابة المقالات العربية، وينشئ برامج لامنهجية. The purpose of this study was to find out about the speaking skills learning planning program and to find out the implementation program for speaking skills learning. 3. To find out about the writing skills learning planning program and to find out the writing skills implementation program. This study is descriptive qualitative. Data collection was carried out by: observation, interviews and documentation. The results of this study are: 1. Planning an Arabic speaking skills learning program starting from: formulating objectives, scheduling Arabic language subjects, preparing competent teachers, compiling programs, determining the right media, and determining the right method. 2. Implementation of the Arabic speaking skills learning program: memorizing 5 Arabic vocabulary words every morning, students write oral vocabulary in notebooks, teachers and students are appointed to supervise the language, giving punishment to students who do not speak Arabic, repeating pronunciation and memorizing vocabulary before the Asr prayer every day. 3. Planning an Arabic writing skills learning program: analyzing students' initial abilities, determining objectives, determining the right method, determining the right measuring or evaluation tool. 4. Implementation of Arabic writing skills learning program: every morning students write 5 vocabulary words, every day before Asr prayer the teacher explains the rules for writing correct vocabulary, holds Arabic essay writing competitions, creates extracurricular programs.